ANALISIS KELAYAKAN USAHA PENGOLAHAN GAHARU DARI KABUPATEN ASMAT - Dwi Iriana; Dwidjono Hadi Darwanto; Slamet Hartono (Agro Ekonomi, 2014)
Feasibility analysis/study is a way to determine the feasibility of the business in terms economic , technical, and financial. The result of this analysis can give benefit as a guide for entrepeneurs, farmers, government to etermine the investment decision. This research/thesis aim to examine the aloes processing aspect, such as: production, managerial, commercial, economic value, environmental impact the aloes marketing chain, and analyze the feasibility of pig aloes processing of Asmat district.This study uses financial analysis, including : Net Present Value (NPV), Net B/C Ratio, Internal Rate Of Return (IRR), Break Event Point (BEP), Payback Period (PP), Sesitivity analysis was also performed, considering the uncertainrty in the parameters and cultivation analysis as comparison of aloes business in nature exploitation.The result of this study show that business of aloes pig processing of Asmat is feasible. If the business activity was conducted in Asmat district with an estimate investment costs increased by 200% the business is feasible. It is recommended to carry out does cultivation in order to preserve the forest, aloes host tree preservation, and sustainability of the aloes processing business.